SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KAMERA DIGITAL BERDASARKAN SPESIFIKASI PERFORMA MENGGUNAKAN METODE SAW - ELLA DIKA; Yusra Fernando (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid advancement of digital camera technology has led to a wide variety of products with diverse specifications, making it difficult for users to determine which camera best suits their needs. Therefore, a decision support system is needed to help users select the best camera objectively and systematically. This study aims to apply the Simple Additive Weighting (SAW) method in the process of selecting a digital camera based on several criteria, namely price, camera resolution, night vision, image quality, camera and lens type, and storage media. The SAW method was chosen because it can perform normalization and weighting of each criterion, thereby generating preference values as the basis for determining the best alternative. The data used in this study was processed through the stages of decision matrix formation, normalization, weighting, and alternative ranking. The results show that the Sony Alpha A6000 camera obtained the highest preference value of 0.7937, making it the recommended best alternative based on the specified criteria. Thus, the application of the SAW method can help users determine their choice of digital camera more effectively, systematically, and objectively.